ヤマト サンミャク ノ キバン ガンルイ ノ K, Rb, Sr, Th, U ノ ソンザイ リョウ - 白石, 和行; シライシ, カズユキ; 金谷, 弘; カナヤ, ヒロシ; Shiraishi, Kazuyuki; Kanaya, Hiroshi (1983)
P(論文) やまと山脈の基盤岩類からのべ63個の試料を選び, Rb, Sr, Th, Uの定量分析を行った。3種の閃長岩類を観察すると, これら元素の存在量や存在比について, 比較的顕著な差異のあることが認められる。特に, 単斜輝石石英モンゾニ岩におけるSrの濃集が著しい。また, 変成岩類相互の差異は必ずしも顕著ではなく, 全体の傾向は, 世界の盾状地での下部グラニュライト相-上部角閃岩相の変成岩の示すこれらの値と大きくかけ離れるものではない。 Sixty-three samples of basement rocks collected from the Yamato Mountains were analyzed for the trace elements Rb, Sr, Th and U together with K. The element abundances and ratios are different among the syenitic rocks. The Sr content of the clinopyroxene quartz monzonite, in particular, is considerably high. Mutual differences of the element abundances and ratios among the metamorphic rocks are not significant, and the ranges of the values seem to be consistent with those of lower granulite to upper amphibolite facies rocks in the shield areas of the world. departmental bulletin paper